COMPREHEND THE THEORY AND CONCEPT OF ENTREPRENEUR COMPETENCY - Wahyudi Henky Soeparto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2017)
Entering the 21st century, there are many major changes in business practices for both the pioneering scale and the scale of its development. Entrepreneurs are thinking hard in creating competitive advantage. Various kinds of management technologies and concepts that already available have been already applied to their business. So far, although they have applied intensely and massively, it hasn’t shown on the performance of their business. The concept of "Amati, Tiru, dan Modifikasi (ATM)" has been done by their competitors. So the alternative that possible to have a competitive advantage is through creating knowledge, attitudes, and behavior of human resources, so that creativity and innovative mindset can appear on any individual within the business organization. Many companies and organizations in Indonesia have implemented a competency-based management system. Two factors that greatly affect a person's competence are: a) Genetic factors that are genetic (internal factors), b) Factors that affect cumulatively from small to adult, for example: education and experience. The economic development of a state will increase if the people who become entrepreneur needed a proportion of 2%. So to fulfill that proportion, Indonesians who became entrepreneur are 4.8 million people. The purpose of applying individual competencies within a company or organization is to improve the internal performance of a company or organization to create competitive advantage while increasing productivity and efficiency.